Formulation and in vitro Evaluation of In-situ Gelling Liquid Suppositories for Naproxen - Noor N. Al-Wiswasi; Eman B.H. Al-Khedairy (College of Pharmacy University of Baghdad, 2017)
In-situ gelation is a process of gel formation at the site of application, in which a drug product formulation that exists as a liquid has been transformed into a gel upon contact with body fluids. As a drug delivery agent, the in-situ gel has an advantage of providing sustained release of the drug agent.  In-situ gelling liquid suppositories using poloxamer 188 (26-30% W/W) as a suppository base with 10% W/W naproxen were prepared, the gelation temperature of these preparations were measured and they were all above the physiological temperature. Additives such as polyvinylpyrrolidin "PVP" ,hydroxylpropylmethylcellulose  "HPMC", sodium alginate and sodium chloride were used in concentration ranging from (0.25-1%W/W) to modulate the gelation temperature and gel strength .The best preparation was obtained through using a combination of poloxamer 188, sodium alginate, naproxen and distilled water (29,0.5,10and 60.5 % W/W respectively)with gelation temperature of 33.6ÂºCÂ±0.2 and gel strength of 28Â±2 seconds. The release of drug from this preparation was sustained for about 12 hours and it was faster than conventional solid suppository (ProxenÂ® 500) and oral tablets (NaproxenÂ®500) using dialysis tubing method. Key words: - naproxen, in-situ gelation, liquid suppository, poloxamer188